2023
DOI: 10.3389/fragi.2023.1231706
|View full text |Cite
|
Sign up to set email alerts
|

The dual face of microglia (M1/M2) as a potential target in the protective effect of nutraceuticals against neurodegenerative diseases

Samar F. Darwish,
Abdullah M. M. Elbadry,
Amir S. Elbokhomy
et al.

Abstract: The pathophysiology of different neurodegenerative illnesses is significantly influenced by the polarization regulation of microglia and macrophages. Traditional classifications of macrophage phenotypes include the pro-inflammatory M1 and the anti-inflammatory M2 phenotypes. Numerous studies demonstrated dynamic non-coding RNA modifications, which are catalyzed by microglia-induced neuroinflammation. Different nutraceuticals focus on the polarization of M1/M2 phenotypes of microglia and macrophages, offering a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 228 publications
0
5
0
Order By: Relevance
“…However, if overactivated, neuroinflammatory and neurodegenerative disorders may ensue [ 65 , 67 , 68 , 70 ]. In general, depending on their activation phase, they are categorized as M1 microglia, which lead to neuroinflammation and neurotoxicity, and M2 microglia, which stimulate anti-inflammatory and neuroprotective effects [ 69 , 71 , 72 ].…”
Section: Microgliamentioning
confidence: 99%
“…However, if overactivated, neuroinflammatory and neurodegenerative disorders may ensue [ 65 , 67 , 68 , 70 ]. In general, depending on their activation phase, they are categorized as M1 microglia, which lead to neuroinflammation and neurotoxicity, and M2 microglia, which stimulate anti-inflammatory and neuroprotective effects [ 69 , 71 , 72 ].…”
Section: Microgliamentioning
confidence: 99%
“…They also suffer morphological changes, such as losing lengthy processes [45]. Microglial cells were thought to change into the M1 phenotype (proinflammatory) or the M2 microglia (anti-inflammatory phenotype) by releasing chemokines that aid in tissue repair and vascular endothelial growth factor; however, more recent studies questioned this classification, pointing to a fragile line separating the two states [46].…”
Section: Microglia In the Context Of Spinal Cord Injurymentioning
confidence: 99%
“…However, recent studies suggest that differences in microglia functions are not driven exclusively by their milieu, but, rather, by the unique properties they possess. Therefore, it is suggested that microglial subtype categorization be based on their function [ 132 , 141 , 142 ].…”
Section: Glial Cellsmentioning
confidence: 99%